The sound of death rattle II: how do relatives interpret the sound? - Wee, B; Coleman, P; Hillier, R; Holgate, S (2006)
BACKGROUND: In an earlier study, we found that some bereaved relatives (five out of 12 interviewed) found it distressing to hear the sound of death rattle, but the remainder did not. In this paper, we report a second study in which we explored how a different group of relatives interpreted the sound of death rattle when they heard it. METHOD: We conducted face-to-face semi-structured interviews with 25 bereaved relatives using the principles of grounded theory. RESULTS: Seventeen of the 25 bereaved relatives interviewed had heard the sound of death rattle. Ten relatives were distressed by the sound, but seven were not. Some relatives regarded the sound of death rattle as a useful warning sign that death was imminent. Their interpretation of the sound was influenced by the patient's appearance, being less concerned if the patient was not obviously disturbed. Relatives were distressed when they thought that the sound of death rattle indicated that the patient might be drowning or choking. These concerns were reinforced by seeing fluid dribble from the dying patient's mouth. CONCLUSION: This study confirms the previous finding that not all relatives are distressed by the sound of death rattle. It also demonstrates that relatives interpret the sound in a variety of ways, some matter of fact and some distressing. We suggest that effective communication is helpful in uncovering relatives' interpretation of death rattle and dispelling unwarranted fears.